Incidence and risk factors of abdominal surgical site infection in a Nigerian Tertiary Health care centre - Adejumo, Adeyinka Ayodele; Nuhu, Mshelia; Afolaranmi, Tolulope (International Journal of Infection Control, 2015)
This study aims to determine the incidence of and identify the risk factors responsible for surgical site infection (SSI) following laparotomies in adult patients in a Nigerian tertiary care facility. This is a prospective study carried out between January and December 2012. Wound assessment was done using standardized criteria stipulated by the Centres for Disease Control and Prevention. There were 291 patients during the study period, out of which 223 met the inclusion criteria: 157 (70.4%) males and 66 (29.6%) females. Surgical site infection was diagnosed in 85 patients giving an incidence rate of 38.1%. Identified risk factors for SSI include anaemia, contaminated and dirty wounds, retroviral disease status, physiological status (ASA scores IV and V), prolonged surgery time, cadre of surgeon, emergency surgeries and use of drains. The high incidence of SSI observed in this study was found more in patients that presented with septic abdomen and those that had large bowel procedures. Paying close attention to identified risk factors will reduce the burden of SSI.